Study on Determining Perfluorooctanoic Acid and Perfluorooctane Sulfonic Acid in Fishery Products - Bui, Kim Hoan; Do, Thi Thu Hang; Kieu, Thi Lan Phuong; Luu, Thi Huyen Trang; Do, Thi Hong Thuy; Tran, Cao Son; Vu, Hong Son (Engineering and Technology For Sustainable Development, 2024)
In the study, liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used for simultaneous determining perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) in fishery products. QuEChERS method (Quick, Easy, Cheap, Effective, Rugged and Safe), originally developed by Anastassiades, was modified to extract samples. The samples were hydrated and extracted with acetonitrile and formic acid, supported by inorganic salts, matrix co-extracts were removed by C18 and the extracts were passed through OASIS PRiME HLB cartridges. The limit of detection (LOD) and limit of quantification (LOQ) of PFOA and PFOS were 0.016 ng/g, 0.05 ng/g and 0.05 ng/g, 0.15 ng/g, respectively. The recovery ranged from 96.2 – 120%, all repeatability is satisfactory (RSD